INTERRELATIONSHIP OF THYROID HORMONES, OBESITY, AND PROLACTIN IN INFERTILE WOMEN - Kataria, Juhi; Gill, Gurpreet Kaur; Kaur, Manbir (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â  Â Objective: The aim of the study was to evaluate and compare the level of thyroid hormones, namely, triidothyronine (T3), thyroxine (T4), thyroid-stimulating hormone (TSH), and prolactin in blood serum of infertile women with normal healthy subjects in Amritsar region of Punjab, India. A number of complications arise from the dysfunction of hypothalamic-pituitary-ovarian axis, which leads to the hormonal disturbances in female reproductive system. Certain disorders such as obesity and thyroid hormone imbalance are highly prevalent and lead to various complications in pregnancy such as polycystic ovary syndrome. These disorders lead to the infertility and ultimately constitute a major physiological stress. A multidimensional diagnostic approach is imperative in evaluating these disorders. In the present study, the association between thyroid hormones and prolactin has been reviewed in infertile women which is a prerequisite to work up for infertility in Punjab. Methods: Hemoglobin levels were estimated in the blood serum of healthy controls and infertile women by the method of Sahli. The levels of serum T3, T4, TSH, and prolactin were determined by electrochemiluminescence immunoassay using Cobas e 411 analyzer according to the instruction manual. Results: Majority of infertile women were found to have hypothyroidism and hyperprolactinemia which can be correlated with infertility. This condition might respond to the treatment for their hormonal and prolactin levels, and fertility can be restored. Conclusion: The measurement of TSH and prolactin should be done at an early stage of infertility rather than more invasive procedures involved in the treatment of infertility in women.